Cross-sector collaboration between ranchers and farmers in waste utilization to achieve sustainable food - Muhammad Mulky Rasyha Raikaramdan; Aisyah Mutiara Rahmat; Marshi Truly Sadhana (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2026)
Background: Indonesia's food security still faces various obstacles, including a meat production deficit, feed price fluctuations, and declining soil quality due to the use of chemical fertilizers. This study aims to review opportunities for collaboration between farmers and ranchers in the utilization of waste to support a sustainable food system. Methods: This study uses a descriptive qualitative approach through literature study and conceptual analysis, examining scientific sources related to food security, waste utilization, and the integration of agriculture and animal husbandry. Findings: The utilization of livestock manure as organic fertilizer and corn stalks as silage feed increases resource efficiency and also demonstrates environmental awareness, such as improving soil quality and reducing dependence on imported fertilizers and feed. Collaboration through the KPPKP Food Security Care Farmer-Livestock Breeder Group strengthens relationships between policy makers, academics, and the community in supporting sustainable production. Conclusion: The integration of waste utilization between farmers and ranchers has the potential to strengthen national food security through the optimization of local resources. Novelty/Originality of this article: This study proposes a model of cross-sector collaboration based on structured waste utilization through the KPPKP institution as a strategic link between all parties.